Demographic Characteristics And Medication Adherence In Patients With Pulmonary Tuberculosis - Sri Mala Hayati; Ade Kartika (Jurnal EduHealth, 2024)
Pulmonary Tuberculosis is a chronic infectious disease that is contagious and can lead to illness and death. To date, no country has been free from pulmonary TB, although the incidence of pulmonary TB has decreased and requires long-term treatment. The purpose of this study is to understand the characteristics and medication adherence of pulmonary TB patients. This study employs a quantitative research method with a descriptive research design, using a sample size of 70 individuals. The results show that the majority of respondents are elderly, The results of the study showed that the majority of respondents had an elderly age of 44 (62.85%), male sex with 44 people (68.6%), married status majority with 47 people (71.4%), had incomes below 500,000 to 1,500,000 with 49 people (70%) and the majority of respondents had never received health education with 56 people (80%). In addition, the results showed that as many as 58 people had pulmonary TB patients. has low compliance with a percentage of 82.8%